2017
DOI: 10.1021/acs.jnatprod.6b00950
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antiosteoporotic Natural Product Lead Compounds That Inhibit 17β-Hydroxysteroid Dehydrogenase Type 2

Abstract: 17β-Hydroxysteroid dehydrogenase type 2 (17β-HSD2) converts the active steroid hormones estradiol, testosterone, and 5α-dihydrotestosterone into their weakly active forms estrone, Δ4-androstene-3,17-dione, and 5α-androstane-3,17-dione, respectively, thereby regulating cell- and tissue-specific steroid action. As reduced levels of active steroids are associated with compromised bone health and onset of osteoporosis, 17β-HSD2 is considered a target for antiosteoporotic treatment. In this study, a pharmacophore m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…For the two most potent compounds, IC 50 values were determined. Ethylparaben and ethyl vanillate inhibited 17β-HSD2 with an IC 50 of 4.6 ± 0.8 µM and 1.3 ± 0.5 µM [ 19 ], respectively ( Figure 4 B). A mixture of ethyl- (6 µM) and hexylparaben (12 µM) showed additive effects in terms of 17β-HSD2 inhibition compared to each individual compound ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two most potent compounds, IC 50 values were determined. Ethylparaben and ethyl vanillate inhibited 17β-HSD2 with an IC 50 of 4.6 ± 0.8 µM and 1.3 ± 0.5 µM [ 19 ], respectively ( Figure 4 B). A mixture of ethyl- (6 µM) and hexylparaben (12 µM) showed additive effects in terms of 17β-HSD2 inhibition compared to each individual compound ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of 6 μM ethyl- (2-P) or 12 μM hexylparaben (6-P) or a mixture of both compounds on 17β-HSD2 activity was assessed in lysates of transiently-transfected HEK-293 cells. Dimethylsulfoxide (DMSO) vehicle served as a negative control and nordihydroguaiaretic acid (NDGA) as a positive control [ 19 ]. Experiments were performed three times, independently.…”
Section: Figurementioning
confidence: 99%
“…In line with this 17β-HSD2 is more and more considered as target for antiosteoporosis treatment. In an in vitro assay using lysates of cells expressing the recombinant human enzyme 17β-HSD2, Vuorinen et al (2017) tested 36 hit molecules, including 44 and 73 from E. laurentii. These compounds with respective IC 50 values of 1.52 and 2.03 µM were among the most active 17β-HSD2 inhibitors tested.…”
Section: Antiosteoporosis Activitymentioning
confidence: 99%
“…These compounds with respective IC 50 values of 1.52 and 2.03 µM were among the most active 17β-HSD2 inhibitors tested. However, they selectively inhibited 17β-HSD1 (that catalyzes the reverse reaction) over 17β-HSD2 and therefore cannot be suitable lead structures for a possible therapeutic use (Vuorinen et al, 2017).…”
Section: Antiosteoporosis Activitymentioning
confidence: 99%
“…Osteoporosis is a highly prevalent bone disease caused by an inappropriate rate of bone resorption compared with bone formation, and the characterization of novel compounds with anti-osteoporotic potential is of high interest [33,34,35,36]. Yodthong et al reported that L-quebrachitol promoted the proliferation, differentiation, and mineralization of pre-osteoblastic MC3T3-E1 cells by triggering the bone morphogenetic protein-2 (BMP-2)-response, as well as the runt-related transcription factor-2 (Runx2), mitogen-activated protein kinase (MAPK), and Wnt/β-catenin signaling pathway [37].…”
mentioning
confidence: 99%